2023
DOI: 10.1002/dmrr.3736
|View full text |Cite
|
Sign up to set email alerts
|

Simple proxies of insulin resistance identify obese metabolic dysfunction‐associated fatty liver disease subjects with advanced liver disease

Giovanni Petralli,
Antonio Salvati,
Domenico Tricò
et al.

Abstract: AimsInsulin resistance (IR) plays a pivotal role in the pathogenesis of Metabolic dysfunction‐Associated Fatty Liver Disease (MAFLD), which can progress to liver fibrosis. We examined the relationship of different IR scores with markers of MAFLD severity in obese individuals.Materials and MethodsIn this retrospective observational study, 346 non‐diabetic, overweight/obese individuals with newly diagnosed MAFLD (age 50.2 ± 13.3 years, 34% females, BMI 30.8 ± 4.4 kg/m2) underwent liver stiffness (LS) and control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, thiazolidinediones that lower adipose tissue dysfunction, insulin resistance, and in ammation are proven to be advantageous in these patients (Musso et al, 2017). The studies utilizing pioglitazone have shown amelioration in insulin resistance as well as in histology and laboratory ratio of liver function in patients with fatty liver (Lingvay et al, 2021;Petralli et al, 2023; M. J. . This study aimed to determine the effect and safety of pioglitazone, metformin, and ertugli ozin in NAFLD with type 2 diabetes mellitus (T2DM).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, thiazolidinediones that lower adipose tissue dysfunction, insulin resistance, and in ammation are proven to be advantageous in these patients (Musso et al, 2017). The studies utilizing pioglitazone have shown amelioration in insulin resistance as well as in histology and laboratory ratio of liver function in patients with fatty liver (Lingvay et al, 2021;Petralli et al, 2023; M. J. . This study aimed to determine the effect and safety of pioglitazone, metformin, and ertugli ozin in NAFLD with type 2 diabetes mellitus (T2DM).…”
Section: Introductionmentioning
confidence: 99%